Electrospun nanoscale iron oxide-decorated carbon fiber as an efficient heterogeneous catalyst for activating percarbonate to degrade Azorubin S in water. (April 2021) - Hsiao, Chia-Yu; Hung, Ching; Kwon, Eilhann; Huang, Chao-Wei; Huang, Chih-Feng; Lin, Kun-Yi Andrew
Highlights: Fe2 O3 @ carbon fiber (FeCF) is derived from carbonization of Fe(acac)3 -PAN fiber. FeCF shows a higher catalytic activity than Fe2O3 for activating PC to degrade AZS. FeCF exhibits Ea of 39 kJ/mol for AZS degradation, which is lower than reported Ea . FeCF can be reusable and remain catalytic active for activating PC to degrade AZS. Abstract: Sodium percarbonate (2Na2 CO3 ∙3H2 O2 ) (PC) represents a promising alternative to H2 O2 as PC is solid-phase, making it easier to handle; however iron (Fe) species are usually necessitated to activate PC for effectively producing hydroxyl radicals (HR) in degradation of toxicants. As homogeneous Fe species leads to severe issues of precipitation, heterogeneous iron oxide nanoparticles (NPs) seem promising but these NPs tend to aggregate in water. Thus, it is critical to develop supported iron oxide NPs. Since carbonaceous materials are one of the most useful supports, carbonaceous materials can be even fabricated into special morphologies to support iron oxide NPs. Herein, we propose to employ the electrospinning technique to develop carbon fiber (CF) as an advantageous carbon support because CF has a large aspect ratio (50:1) to allow iron oxide NPs well decorated on CF, forming a promising iron oxide NP-decorated CF (FeCF) for PC activation. FeCF is characterized using SEM, TEM, XRD, XPS, Raman spectroscopy and N2 sorption isotherm. This FeCF can exhibit a noticeably higher catalytic reactivity than pristine Fe2 O3 NPs for activating PC to generate HR, and then degrade a toxicant, Azorubin S (AZS). FeCF also exhibits a much lower activation energy ( Ea ) value of AZS degradation than other reported catalysts. Besides, FeCF could be also reusable to activate PC for degradation of AZS. Additionally, the degradation mechanism of AZS by FeCF-activated PC is also elucidated to provide insights into activation of PC and its environmental applications. These features prove that FeCF is an efficient heterogeneous catalyst to activate PC for degrading toxicants in aqueous solutions.